Forecast of China’s Annual Carbon Emissions Based on Two-Stage Model - Zhang, Xiaolei; Xiong, Jingbo; Song, Jianqi (Frontiers in Environmental Science, 2022)
China's carbon emissions are a key issue in the world. At present, China has put forward a clear "dual-carbon" goal, of which the first target is to reach the peak of carbon emissions by 2030. To solve this problem, this paper proposes a two-stage method for forecasting China's annual carbon emissions, which is combined with relevant data affecting carbon emission data to predict China's annual carbon emissions. Through the study of this article, we found the related factors affecting China's carbon emissions data, and based on these factors using two-stage method, we predict the next year carbon emissions data. Compared with the real data of China's annual emissions from 2017 to 2020, the predicted intervals form this method can cover the real data well. On the one hand, the key factors for predicting carbon emission data are found with this method, and on the other hand, the effectiveness of this method is verified. Based on the result of this method, it provides support for later policy making and adjustment.